Children and adolescents with obesity and the metabolic syndrome have high circulating cortisol levels. - Sen, Yasar; Aygun, Denizmen; Yilmaz, Erdal; Ayar, Ahmet (My University, 2008)
OBJECTIVES: The aim of this study was to investigate the relationship between the varying degrees of obesity and blood glucocorticoid levels in obese children and adolescents with and without metabolic syndrome features. METHODS: We studied 241 obese children and adolescents aged between 2 and 17.6 years; 127 boys and 114 girls. All children underwent an oral glucose tolerance test. Measurements included blood pressure, cortisol, ACTH, and lipid profiles. The diagnosis of metabolic syndrome was defined according to the criteria adapted from World Health Organisation and National Cholesterol Education Program Adult Treatment Panel-III guidelines. RESULTS: Blood cortisol and ACTH levels were higher in patients with MS than without MS (p = 0.02). ACTH levels increased with weight (r = 0.13, p = 0.02), systolic blood pressure (r = 0.21, p = 0.002), diastolic blood pressure (r = 0.17, p = 0.01), fasting glucose (r = 0.17, p = 0.01). Cortisol production was only correlated with systolic blood pressure (r = 0.12, p = 0.05). CONCLUSIONS: Results from the present study indicates that there may be a link between cortisol production and the metabolic syndrome in obese children and adolescents.
Keywords: Adolescent; Adrenocorticotropic Hormone; Blood Pressure; Child; Child, Preschool; Female; Humans; Hydrocortisone; Lipids; Male; Metabolic Syndrome X; Obesity; Risk Factors; corticotropin; hydrocortisone; lipid; adolescent; article; blood; blood pressure; child; comparative study; female; human; male; metabolic syndrome X; obesity; pathophysiology; physiology; preschool child; risk factor